The Prevalence of Learning Styles Theory in Kansas K-12 Classrooms: A Statistical Analysis - Alan English (The Advocate, 2021)
Despite a lack of empirical evidence to support its existence, previous literature has demonstrated that Learning Styles Theory (LST) enjoys widespread popularity in education, leading many researchers to refer to it as a “myth”. This study utilized original survey data to determine Kansas K-12 teachers’ level of predilection for LST. Kansas teachers’ responses (n=147) were analyzed in comparison to that of non-Kansas teachers (n=93) in seven independent Learning Styles Theory measures. Results suggested that Kansas teachers responded statistically less-favorably to the prospect that LST is best for student learning, less likely to view LST as essential for effective instruction, and less likely to identify with a specific learning style than non-Kansas teachers (p<.05). Despite these positive trends, LST remained firmly supported by Kansas and non-Kansas teachers alike.
Keywords: Learning Styles Theory; Kansas K-12 education; pedagogy; teacher education